Red, white, and whole - LaRocca, Rajani (Quill Tree Books, an imprint of HarperCollinsPublishers, 2021)
"Reha feels torn between two worlds: school, where she's the only Indian American student, and home, with her family's traditions and holidays. But Reha's parents don't understand why she's conflicted--they only notice when Reha doesn't meet their strict expectations. Reha feels disconnected from her mother, or Amma, although their names are linked--Reha means "star" and Punam means "moon"--but they are a universe apart. Then Reha finds out that her Amma is sick. Really sick. Reha, who dreams of becoming a doctor even though she can't stomach the sight of blood, is determined to make her Amma well again. She'll be the perfect daughter, if it means saving her Amma's life"--